PENGOPTIMALAN PERAN KEPALA SEKOLAH SEBAGAI MEDIATOR KONFLIK DI SMA NEGERI 2 DEDAI - Sosialisman, Sosialisman; Suharto, Suharto; Junanto, Tulus (Universitas Muhammadiyah Surakarta, 2023)
SMA Negeri 2 Dedai experiences various kinds of conflicts in the school environment. These conflicts include: Conflict between students, conflict between teachers, conflict between teachers and students and conflict between teachers and parents. The objectives of this study are (1) to determine the impact of conflict on school performance and student welfare at SMA Negeri 2 Dedai, (2) to develop appropriate strategies in handling conflicts at SMA Negeri 2 Dedai. and (3) to improve the quality of conflict management at SMA Negeri 2 Dedai by optimizing the role of the principal as a conflict mediator. The benefits of the research are (1) Providing an understanding of the importance of handling conflicts at SMA Negeri 2 Dedai, (2) Providing appropriate solutions in handling conflicts at SMA Negeri 2 Dedai, and (3) Improving the role of the principal as a conflict mediator at SMA Negeri 2 Dedai. Descriptive qualitative research approach was used in this study. This research used purposive random sampling technique and this research utilized observation, interview, and document analysis instruments. Data analysis is in the form of data collection, data reduction, data presentation, and conclusion or verification. The results of this study present findings regarding conflicts found in SMA Negeri 2 Dedai. The forms of conflict that occur are interpersonal, intragroup, and intergroup conflicts. The types of conflicts that researchers get 1) Conflicts between students. 2) Conflict between students and teachers 3) Conflict between teachers and parents and 4) Conflict between teachers and teachers. It is hoped that the results of this study can provide valuable insights for principals, teachers, and school staff in improving their ability to manage conflict at SMA Negeri 2 Dedai.